Study on Failure Difference of Hard Rock Based on a Comparison Between the Conventional Triaxial Test and True Triaxial Test - Zheng, Guoqiang; Tang, Yonghui; Zhang, Yan; Gao, Yaohui; Zhu, Guoqiang; Gao, Meiben; Ren, Junqian; Chen, Kezhu; Sun, Jicheng (Frontiers in Earth Science, 2022)
The study on the failure difference of deep hard rock based on the comparison between conventional and true triaxial tests can help us better understand the fracture processes and failure characteristics of the deep rock mass. Therefore, this article carries out a comparative analysis of the failure of hard rock under conventional and true triaxial stress states. Within the scope of this study, it is found that the brittle–ductile transformation properties can be intuitively reflected in the rock stress–strain curve and failure mode. The brittle–ductile transition point of rock can also be determined by the difference between peak and residual strengths. The rock failure strength increases with the increase of σ2, the peak strain decreases with the increase of σ2, the stress drop of the post-peak curve becomes more obvious with the increase of σ2, and the rock tends toward Class II brittle failure after the peak with the increase of σ2. When σ3 is relatively high, the rock fracture angle increases with the increase of σ2 with obvious regularity. Compared with conventional triaxial stress conditions, the differential stress-induced anisotropy failure is the biggest difference in rock fracture characteristics between true and conventional triaxial stress states. This study can supply useful references to the study of failure properties of hard rock under complex stress states.